A Comparison of Weighted and Unweighted Intergroup Climate Satisfaction Scores - Barth, R. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
Perceptions of the configuration and quality of intergroup climates by 256 engineer-scientists in ten R & D organizations were factor analyzed. Five reliable dimensions evolved which accounted for 65% of the 68-item total variance. For each of these dimensions, the relationships between three combinations of level of attainment, level of aspiration, and level of urgency are explored separately and the combined impact of each combination on overall satisfaction with intergroup communication is examined. The findings suggest that unweighted scores provide better predictors of overall satisfaction with intergroup communication than do scores weighted by urgency ratings. Results lend empirical weight to studies in which the utility of weighted versus unweighted scores in the prediction of job satisfaction were explored.